(untitled) (Scientific journal of the Fergana State University, 2025)
This article studies the purification of thermally stable salts from (methyl)diethanolamine used for the purification of natural gas using sorbents. The purification of working solutions of methyldiethanolamine on ion exchange resins is considered an effective method, using AB-17-8 anionite. Pseudo-first and pseudo-second order kinetic models were used to evaluate the kinetics and adsorption mechanism.